PENGARUH TINGKAT PENCAPAIAN PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI KOTA PALEMBANG - Nina Fitriana (JURNAL KOMPETITIF, 2014)
Human resources is an important element in economic growth. To improve the quality of human resources then education has a very important role.This study aimed to examine the influence of the level of educational attainment on economic growth of Palembang.The data used in the form of time series in 1992-2011 to obtain a description of the influence level of educational attainment on economic growth Palembang cityÃ‚Â  with analysis OLS (Ordinary Least Square). Recursive models are used to see the effect of the level of educational attainment on economic growth Palembang CityThe results showed that the level of educational attainment, changes in GDP per capita the previous year and the change in the number of teachers the previous year significantly affect the level of educational attainment. Educational attainment level estimation results, the number of schools significantly affect education spending. Furthermore, the education expenditure estimates, the inflation rate and the unemployment rate significantly affects the GDP per capita of Palembang.Ã‚Â Keywords: Educational achievement, Economic growth.Ã‚Â